The effects of a high school curriculum reform on university enrollment and the choice of college major - Katja Görlitz; Christina Gravert (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2015)
This paper evaluates the effects of a high school curriculum reform on students probability to enroll at university and to choose Science, Technology, Engineering or Mathematics (STEM) as college major. The reform that was introduced in one German state increased the degree of difficulty to graduate from high school by increasing the mandatory instruction time in the core subjects German, a foreign language, mathematics and natural sciences and by raising the graduation requirements. Based on administrative data covering all students, the empirical analysis is carried out by applying a difference-in-differences model. The results show that the reform increased university enrollment rates for both gender. With regard to choosing STEM as college major, we only find a robust positive effect for males.
Keywords: I21; I23; I28; 330; high school curriculum; university educational decisions; the choice of college major; STEM; reform evaluation